Internalisasi Nilai-nilai Sosio-kultural dalam Pembelajaran Agama Islam di Perguruan Tinggi Kota Palopo - Arini Ulfah Hidayati; Dedi Andrianto; Yunus Yunus; Mukhlisin Mukhlisin (Bustanul Ulum Journal of Islamic Education, 2023)
The phenomenon of violence shown that humans have failed to understand heterogeneity and diversity. This study aims to determine the internalization values of Bugis culture in Islamic education at Andi Djemma University and IAIN Palopo. This study uses a qualitative method with an ethnopedagogical approach. The results showed that internalisation values of Bugis culture in Islamic higher education is in line with multiculturalism values that grow and develop in Indonesia. Some of the  local wisdom values in Bugis culture are manifested in the concept of Tudang Sipulung and living value method. The internalisation values of Bugis culture in learning of Islamic religious education provides respectful values such as Sipakatau (mutual information), Sipakalebbi (Mutual Respect), Sipakaingge (Remind each other), Sipakatou (Mutual Sharing). Respect peace, fellow human beings, especially if they are fellow humans. So that Bugis cultural education is in line with the values of pluralism that grow and develop in Indonesia.